(untitled) ([United States], 2014)
Seven mini-movies starring your favorite characters from Despicable Me; Hop; and Dr. Seuss? The Lorax come together for the first time ever in one exciting collection. Get busy with the Minions, hop along with Phil and Carlos, and explore nature with The Lorax in these hilarious crowd- pleasing adventures.
Keywords: Video recordings for the hearing impaired; Video recordings; Short films; Childrens films